Desenvolvimento de sistemas bionanohíbridos a base de sólidos inorgânicos lamelares e matrizes biopoliméricas como sistemas dispensadores de espécies de interesse farmacológico. - LEITE, Mayara Santos (2019)
The present work reports the synthesis, characterization and the evaluation of the bionanocomposite systems based on layered clays and biopolymers as nanodevices for transport and release of ciprofloxacin. For this study, hybrid materials were prepared through the intercalation of ciprofloxacin into layered double hydroxide and montmorillonite clay employing the co-precipitation and ion exchange reaction, respectively. In order to protect the resulting ciprofloxacin-clay hybrids against the gastrointestinal fluids, these intercalation compounds were incorporated into a biopolymer mixture based on i-carrageenan polysaccharide and gelatin protein forming bionanocomposites systems, which were conformed as beads through ionic gelification reaction with Ca2+ ions and dried by the freezedried process. Both ciprofloxacin-clay hybrids and bionanocomposites were characterized by means of different experimental techniques, such as XRD, FTIR, TG/DTA and SEM. In order to evaluate the freeze step, bionanocomposite beads were freezing by conventional freeze (-20 ºC) or liquid N2 (-196.1 ºC), and the in vitro studies of release of ciprofloxacin demonstrated that the release kinetics is significantly influenced by the process of freezing, where a difference in the release profiles mainly in fluids that simulate the intestinal zone (pH 6.8 and 7.4). These results point out bionanocomposite systems based on layered solids and biopolymers can act as drug delivery nanodevices, where the release of the active principle can be modulated depending on the freezing method of the bionanocomposite gel becoming a promising material for the biomedical area.